Commodity Outlook 2003: U.S. and World Sugar Markets - Andrew Schmitz (EDIS)
This paper provides an overview of U.S. sugar policy and the importance of the European Union (E.U.) and Brazil in the world sugar market. Both U.S. and E.U. sugar policies support sugar prices for growers well above world levels. Brazilian sugar producers are supported by their government sugar-ethanol program in which over 50 percent of the sugarcane grown in Brazil is converted into fuel. Sugar prices for U.S. and E.U. producers should remain at the current levels. World sugar prices should remain at near record low levels. This is EDIS document FE375, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.